To turn the whole world over : Black women and internationalism - Blain, Keisha N., 1985-; Gill, Tiffany M.; West, Michael O. (Michael Oliver) (Black internationalism., 2019)
"To Turn the Whole World Over: Black Women's Internationalism in Historical Perspective represents the first scholarly attempt to assemble the most recent works on black women's internationalism during the late nineteenth and twentieth centuries. It highlights the range and complexity of black women's global engagements and centers their experiences as key historical actors in shaping internationalist movements and discourses from the 1870s to the 1970s. By analyzing the gendered contours of black internationalism, this collection of essays engages these two key questions: (a) how was black women's engagement in internationalism similar to and/or different from their male counterparts? (b) To what extent did black women merge internationalism with issues of women's rights and/or feminist concerns? Furthermore, the anthology calls for a re-conceptualization of black internationalism by asking how black women's lives and experiences alter the ways narratives of the global black freedom struggle are articulated. This anthology, then, does more than expand the paucity of scholarship on black women and internationalism. It is both an assessment of the field as well as an attempt to expand the contours of black internationalism theoretically, spatially, and temporally"--